The Role of the Book Al-Muqaddimah al-Jazariyyah in Developing Arabic Speaking Skills - Hasbi, Anang Fajar; Syukri, M.; Maida, Nining; Farkhan, Muhammad (Journal of Arabic Language Studies and Teaching, 2026)
This study examines the role of Al-Muqaddimah al-Jazariyyah in developing students’ Arabic speaking skills within the pesantren context, addressing the limited attention to its pedagogical potential beyond tajwīd instruction. This research employs a qualitative approach with an exploratory case study design at Pondok Pesantren Azzilfa. Data were collected through classroom observations, in-depth interviews with teachers and students, and documentation of instructional activities. The findings reveal that the use of Al-Muqaddimah al-Jazariyyah contributes significantly to improving students’ speaking skills, particularly in phonological accuracy, articulatory fluency, and speaking confidence. Instructional practices such as talaqqī, memorization of nazham, simā‘an, and muḥādathah effectively integrate tajwīd-based phonological mastery with communicative language use. Furthermore, reinforcement of makhārij al-ḥurūf and Arabic sound characteristics provides a strong phonetic foundation for more accurate and confident oral expression. These findings suggest that classical Islamic texts can function as strategic pedagogical resources when combined with communicative approaches, offering a sustainable model for Arabic language learning in pesantren.